Pengaruh Kemampuan Derivatif dan Literasi dalam Matematika Ekonomi terhadap Keputusan Investasi Mahasiswa Program Studi Manajemen - Alma Noviana; Andreas Alfa Morino; Hasan Almawardi; M.Pajri Ade Pratama (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of derivative skills and literacy in economic mathematics on investment decisions of students in the Management Study Program. The study was conducted using a quantitative approach using primary data collected through questionnaires distributed to students. The collected data were then analyzed using multiple regression tests to determine the extent to which the studied variables influence investment decisions. The results of the multiple regression test indicate that derivative skills and economic mathematics literacy simultaneously have a significant influence on students' investment decisions. The coefficient of determination (R²) value is 0.551, which means that 55.1% of the variability in investment decisions can be explained by these two independent variables, while the remaining 44.9% is explained by other factors not examined in this study. This figure indicates that students' ability to understand and use economic mathematics concepts, especially in terms of derivatives, as well as their financial literacy, play an important role in forming rational and informed investment decisions. The results of this study indicate that mastery of economic mathematics concepts, especially derivative skills, has a direct impact on students' ability to make better and more logical investment decisions. On the other hand, financial literacy also influences how students assess and manage investments, resulting in wiser decisions. Therefore, it is important for educational institutions to integrate mathematical economics and financial literacy into their curricula to help students make more rational investment decisions and reduce potential future financial risks. Furthermore, this study also suggests the need to improve students' understanding of basic concepts in mathematical economics and financial literacy. Management study programs can strengthen their curricula by providing more in-depth training in the applications of mathematical economics, such as the use of derivatives in investment analysis.